Market Share Analysis of Aqua Brand Drinking Water with Markov Chain Approach on PT. X Employees - Yulia, Tri Vanti Devi; Mas'ud, M. Imron (Journal Knowledge Industrial Engineering (JKIE), 2024)
PT. Tirta Investama is a company that is involved in the bottled drinking water industry (AMDK). The success achieved by Aqua at that time was followed by the emergence of new players in the bottled water industry.As a result, many brands of bottled water have emerged and competition between producers continues to develop, so companies need to periodically monitor the position of their products against their competitors' products in order to analyze the market share of their products and find out about market changes that occur using one of the Operation Research methods, the Markov Chain method. The purpose of this study is to predict consumer behavior to analyze market share and determine changes in market share through consumer behavior.The results of the Markov chain analysis show that Aqua's market share as the most popular brand turns out to be slowly increasing its market share, starting from 45% in 2020 and then in 2021 to 63.9%. Oasis's market share was originally 2% in 2020 and then increased to 2.9% in 2021. Le Minerale , which was originally 18% in 2020, increased to 19% in 2021.